ENGLISH ROMANTICISM AND IT`S DEVELOPMENT: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article aims at giving an overview on thewhole romantic period. The start of the romantic period, the way it happened, the poets that helped to make this period shine, the background of the poets and the details of the romantic poetry that ruled this era –all of the aspects are described very elaborately in this article. Elements such as imagination, emotion, nature were used very passionately in the romantic poetry. There are more than four poets who wrote romantic poems in this period but only the life and poetry of the significant four poets are written in this article who was William Wordsworth, Samuel Coleridge, John Keats, P. B Shelley. Wordsworth and Coleridge were the very first influencers of the romantic period. This article will guide people in knowing even the little things of the romantic era.